2022
DOI: 10.1088/1748-9326/ac5767
|View full text |Cite
|
Sign up to set email alerts
|

Ecological resilience: what to measure and how

Abstract: The question of what and how to measure ecological resilience has been troubling ecologists since Holling 1973's seminal paper in which he defined resilience as the ability of a system to withstand perturbations without shifting to a different state. This definition moved the focus from studying the local stability of a single attractor to which a system always converges, to the idea that a system may converge to different states when perturbed. These two concepts have later on led to the definitions of engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 97 publications
(64 reference statements)
2
36
0
1
Order By: Relevance
“…Utilization and Industrialization of Urban Construction Waste in China [17,18]. erefore, considering the structural characteristics of the current demolished buildings, it is determined that the demolition of 1 m 2 of buildings will produce about 1.30 t construction waste.…”
Section: Analysis Of the Current Situation Of Resourcementioning
confidence: 99%
“…Utilization and Industrialization of Urban Construction Waste in China [17,18]. erefore, considering the structural characteristics of the current demolished buildings, it is determined that the demolition of 1 m 2 of buildings will produce about 1.30 t construction waste.…”
Section: Analysis Of the Current Situation Of Resourcementioning
confidence: 99%
“…A better understanding of these relationships could help us identify how many and which metrics need to be measured in natural systems [24,25,63]. This is especially true for metrics related to abrupt transitions for which we need to understand the relations between each other but also with other stability metrics [62].…”
Section: (B) Measuring the Resilience Of Complex Systemsmentioning
confidence: 99%
“…In the same way as the stability of ecological communities has been estimated in a variety of ways using many different metrics [24,25,61], this is also true for resilience and more generally for metrics related to catastrophic shifts [62]. This multiplicity of metrics used to quantify the concepts of stability and resilience in ecological studies raises the question of how the different metrics relate to each other [24].…”
Section: Opportunities To Advance Understandingmentioning
confidence: 99%
“…The recent incorporation of genomics can further help assessing and monitoring restoration efforts [75,76]. Since ecosystem degradation or even collapse is connected to loss of resilience, an ambitious goal would be to define a reliable sensing method that provides a measurable index [77,78]. Using as a working definition of resilience, namely the capacity of a system to recover from perturbations, Lenton et al [68] have suggested a practical implementation.…”
Section: Resilience Network and Tipping Pointsmentioning
confidence: 99%